ALYREF links 3′‐end processing to nuclear export of non‐polyadenylated mRNAs. (12th March 2019) - Fan, Jing; Wang, Ke; Du, Xian; Wang, Jianshu; Chen, Suli; Wang, Yimin; Shi, Min; Zhang, Li; Wu, Xudong; Zheng, Dinghai; Wang, Changshou; Wang, Lantian; et al.
Abstract: The RNA‐binding protein ALYREF plays key roles in nuclear export and also 3′‐end processing of polyadenylated mRNAs, but whether such regulation also extends to non‐polyadenylated RNAs is unknown. Replication‐dependent (RD)‐histone mRNAs are not polyadenylated, but instead end in a stem‐loop (SL) structure. Here, we demonstrate that ALYREF prevalently binds a region next to the SL on RD‐histone mRNAs. SL‐binding protein (SLBP) directly interacts with ALYREF and promotes its recruitment. ALYREF promotes histone pre‐mRNA 3′‐end processing by facilitating U7‐snRNP recruitment through physical interaction with the U7‐snRNP‐specific component Lsm11. Furthermore, ALYREF, together with other components of the TREX complex, enhances histone mRNA export. Moreover, we show that 3′‐end processing promotes ALYREF recruitment and histone mRNA export. Together, our results point to an important role of ALYREF in coordinating 3′‐end processing and nuclear export of non‐polyadenylated mRNAs. Synopsis: The RNA‐binding protein ALYREF functions in coupling nuclear export and 3′‐end processing of polyadenylated mRNAs. New data identify a parallel mechanism for ALYREF also linking 3′‐end processing to nuclear export of non‐polyadenylated, replication‐dependent histone mRNAs. ALYREF prevalently binds to a 3′ region of histone mRNAs in an SLBP‐dependent manner. ALYREF promotes histone pre‐mRNA processing by ensuring U7‐snRNP recruitment. The TREX complex facilitates histone mRNA export by recruiting NXF1. 3′‐end processing promotes ALYREF recruitment and histone mRNA export. Abstract : An RNA‐binding protein coupling nuclear export and 3′‐end processing of polyadenylated mRNAs exerts similar function on non‐polyadenylated replication‐dependent histone mRNAs.